2015
DOI: 10.1016/j.apm.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear vibration of functionally graded fiber-reinforced composite laminated cylindrical shells in hygrothermal environments

Abstract: a b s t r a c tThe effect of hygrothermal conditions on the linear and nonlinear free flexural vibration of anisotropic shear deformable laminated cylindrical shells is investigated. The cylindrical shell is made of fiber-reinforced composites (FRCs) with the reinforcement being distributed either uniformly (UD) or functionally graded (FG) of piece-wise type along the thickness of the shells. The motion equations are based on a higher order shear deformation shell theory with a von Kármán-type of kinematic non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Many studies have also been conducted on vibration, bending, and buckling of laminated composite plates [15,[163][164][165]16,[166][167][168][169][170][171], and shells [172][173][174][175][176][177][178][179][180][181] in hygrothermal environments.…”
Section: Shell Structures In Hygrothermal Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have also been conducted on vibration, bending, and buckling of laminated composite plates [15,[163][164][165]16,[166][167][168][169][170][171], and shells [172][173][174][175][176][177][178][179][180][181] in hygrothermal environments.…”
Section: Shell Structures In Hygrothermal Environmentsmentioning
confidence: 99%
“…Malekzadeh and Heydarpour [174] investigated the free vibration behavior of rotating functionally graded cylindrical shells subjected to the temperature change using the first-order shear deformation shell theory. The effects of hygrothermal environmental conditions on the linear and nonlinear free flexural vibration of anisotropic shear deformable laminated cylindrical shells were investigated by Shen and Yang [176], where the cylindrical shell is made up of fiber-reinforced composites with the reinforcement being distributed either uniformly or functionally graded of piece-wise type along the thickness of the shells and the motion equations were derived based on a higher order shear deformation shell theory with a von Kármán-type of kinematic nonlinearity, and the results displayed that the temperature and moisture variations have a moderate effect on the natural frequencies. Biswal et al [178] studied the effects of hygrothermal environmental conditions on free vibration of woven fiber glass/epoxy laminated composite cylindrical shallow shells both numerically and experimentally based on the FEA and the first-order shear deformation shell theory, where the results showed that the frequency of vibration decreases with the increase of temperature and moisture.…”
Section: Shell Structures In Hygrothermal Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear bending of hybrid plates including carbon nanotube reinforcement (CNTRC) embedded in elastic foundations has been researched by Fan and Wang (2017). The fundamental frequency of FGM doubly curved shell embedded in elastic foundation has been presented by Shen and Yang (2015). They discussed the inflence of volume fraction index, Pasternak foundation, curveture ratio, and other parameter on the nonlinear frequency.…”
Section: Introductionmentioning
confidence: 99%
“…(2017a). The fundamental frequency of functionally graded materials (FGM) doubly curved shell embedded in elastic foundation have been presented by Shen et al. (2015).…”
Section: Introductionmentioning
confidence: 99%